Infrastructural Violence: Five Axes of Inequities in Water Supply in Delhi, India - Kumar, Ashok; Singh, Nitin; Cooper, Sarah; Mdee, Anna; Singhal, Shivani (Frontiers in Water, 2021)
Inequity is deeply embedded in the supply of drinking water in Delhi, India. Using the concept of infrastructural violence, this paper exposes how past and present governance of water has resulted in unequal distribution of supply across the city to exclude vulnerable communities from accessing drinking water. This perspective broadens the gaze away from a narrow gaze on the technical and structural aspects of infrastructure to encompass the socio-political dimensions. This paper starts by outlining the history of water supply in Delhi. We then outline five axes of exclusion which can be read as infrastructural violence and explores how aspects of water policy, legislation and planning uphold these injustices. Our discussion centres on how economics, political ideology and power infiltrate governing mechanisms to influence water infrastructure to entrench poverty and marginalisation. Attempts to improve water security for Delhi’s residents face minimal impact without addressing these embedded inequities. Therefore our analysis offers a framework to systematically create awareness of the factors to be addressed enable a more equitable governance of water supply.